PENGARUH SUSTAINABLE LENDING TERHADAP RISIKO KREDIT BANK UMUM KONVENSIONAL DI INDONESIA - Adji Pratikto; Votsal Dian Lestari; Engelbertha E. Silalahi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
Climate change is one of the greatest challenges of the 21st century, threatening the global economy if not properly mitigated. Mitigating climate change requires enormous costs, necessitating the role of the financial services sector in financing sustainable development projects. However, financing sustainable development projects can threaten the stability of the financial system. This research aims to investigate the impact of sustainable lending on credit risk in the banking sector. To investigate this impact on Indonesia, we use a fix effect model with 5 banks from KBMI IV and KBMI III as samples, for 2020-2024. As control variables, we use the Return on Asset (ROA), Capital Adequacy Ratio (CAR), Loan to Asset Ratio, and Total Asset. The results of the study show that sustainable loans have a positive and significant effect on credit risk. This means that banks in Indonesia still consider sustainable loans to have greater risk than conventional loans